Analisis Mekanisme Penetapan Harga Berdasarkan Prinsip-Prinsip Ekonomi Syariah: Studi Kasus di Toko Ayukdiah Jalan Margo Santoso 1 Sangatta Utara - Mulhama Tahir; Imrona Hayati; Achmad Fahruddin (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to analyze the pricing mechanism based on sharia economic principles implemented at Ayukdiah Store in Sangatta Utara. The research employed a descriptive qualitative method with a case study approach. Data collection techniques included observation, interviews, and documentation. The findings reveal that the pricing at Ayukdiah Store combines cost-based pricing and competitor-based pricing methods, while adhering to sharia principles such as tawhid, justice, accountability, honesty, mutual consent, and the prohibition of usury. This strategy not only maintains business competitiveness but also builds customer loyalty and avoids unethical business practices.